A content analysis of Australian television advertising: focus on child and adolescent oral health - Amit Arora; Caroline M. Bowman; Stephanie J. P. Chow; Jack Thepsourinthone; Sameer Bhole; Narendar Manohar (BMC, 2018)
Abstract Background Children's preferences for cariogenic foods and/or drinks has been proven to be associated with exposure to advertisements. This study aimed to assess and compare the proportion of cariogenic food and /or drink advertisements aired on three metropolitan Sydney commercial television channels at different broadcast times during school term and school holidays. Methods Three Sydney free-to-air television channels (Channels Seven, Nine, and Ten) were recorded between June 2016 and January 2017. Two weekdays and one weekend day were recorded for a week for each channel during the school term and school holidays, respectively. All channels were recorded from 0630 h until 2300 h. Food and/or drink advertisements were categorised according to the time they were aired and their sugar and acid content. For each channel, school holiday data was compared with school term data. Pearson chi-squared testing was used to determine the difference in advertisements rates across TV channels and broadcast times including school holidays and school term. Results The proportion of food and/or drink advertisements for all networks was less than 10% of all advertisements. Overall, Channel Ten had the most food and/or drink advertisements (39.74%) and Channel Seven had the lowest (28.60%). Channel Ten aired the largest proportion of food and/or drink advertisements (27.18%) during school term Channel Nine aired the highest number of food and/or drink adverts (15.50%) during school holidays. There were more food and/or drink advertisements during children's viewing hours compared to overlap, adult, and other viewing periods respectively, with Channel Ten airing the highest advertisements (15.72%) and Channel Seven airing the least (11.35%) food and/or drink advertisements. For all analyses, Pearson chi-square tests had a p-value < 0.001. Conclusion Although the overall proportion of food and/or drink advertisements aired on Sydney television is low, the advertisements containing high sugar and /or acid were broadcasted more during children's viewing times than other times and during school term compared to school holidays.